Development of battery intervention power supply for solar roof top installations. Issue 2 (7th January 2019) - Valsala, Kamala Devi; Premkumar, K.; Beevi, A. Bisharathu
Abstract : In India, battery storage and time‐based tariff are yet to be introduced in solar microgrid tied inverters. Here, the authors propose an improved multistage converter topology intended for single phase solar roof top applications with battery storage. It works in six modes depending on solar‐load‐battery‐grid profiles. The whole strategy is implemented in a battery intervention power supply (BIPS) that uses energy storage integrated with the solar generator that helps in smoothing of power, load shifting, load dispatch, and load angle control. Notably, load dispatch decision is arrived based on several independent parameters that take different values at a time. A Boolean equation is derived relating the different parameters so as to arrive at a single decision. This is achieved by a variable entity k‐map. A voltage control is also implemented which is done by load angle control of the inverter current. © 2019 American Institute of Chemical Engineers Environ Prog, 38: 570–583, 2019